Symptoms, haemodynamics, and exercise capacity during long term treatment of chronic heart failure. Experience with pirbuterol. Issue 3 (September 1983) - Dawson, J R; Canepa-Anson, R; Kuan, P; Reuben, S R; Poole-Wilson, P A; Sutton, G C
Abstract : An open study of long term treatment with an oral beta 2 agonist (pirbuterol 20 mg three times daily) was undertaken in 63 patients with severe chronic heart failure. During three months of treatment 20 (32%) patients died, of whom 16 were taking the drug at the time of death. Mortality was related to initial functional class (New York Heart Association classification: 23% in grade III and 75% in grade IV). Concomitant treatment with digoxin did not affect mortality. The drug was well tolerated by most patients but unwanted side effects necessitated withdrawal of the drug in six (10%). Thirty-five patients were continuing to take the drug after three months, of whom 22 reported symptomatic improvement and only four deterioration. There was a relation between symptomatic improvement and increase in exercise capacity. At initial haemodynamic assessment a single dose of pirbuterol increased the cardiac index by 34% and the stroke index by 21%. Left ventricular filling pressure fell by 23% and systemic vascular resistance by 22%. Haemodynamic reassessment after three months of continuous treatment in 29 patients showed maintained improvement in the group as a whole, although individual variation was considerable. There was no apparent relation between haemodynamic improvement and improvement in exercise duration and symptoms. Severe heart failure has a poor prognosis. Identification of those patients who may derive benefit from treatment with a particular drug is not yet possible.